DAYA DUKUNG DAN POTENSI LAHAN UNTUK PENGEMBANGAN TANAMAN PANGAN DI KAWASAN SUB-DAERAH ALIRAN SUNGAI PANASEN KABUPATEN MINAHASA - Dolfie D. D. Tinggogoy; Jailani ., Husain; Sandra ., Pakasi (Sam Ratulangi University, 2016)
The aims of this reserch was analyzing the carrying capacity of the land based on food crops productivity in Panasen sub-watershed areas Minahasa regency, Analyzing land suitability clases for food crops development in Panasen sub-watershed areas Minahasa regency, Knowing the vast potential of land that could be used for food crops development in Panasen sub-watershed areas Minahasa regency and Mapping the land potential at scale of 1: 50,000 for food crops development in Panasen sub watershed areas Minahasa regency. The research method is a survey method, methods overlay is used to create a map of a group of land based on slope maps, land use maps and soil maps. Method of matching (match) is used to determine the grade of land suitability and potential land area of each crop. Statistic methodis used for the carrying capacyti of agriculture land analyzing. The results of the research show that are the carrying capacity of agricultural land is = 2.93. Rice equivalent is 2,93 x 265 kg/ person/year is 776, 45 kg of rice/person/year. Potential land for geared the development of food crops is a rice crops is 3095.10 ha which consists of land suitability classes S3waâ‚‚rcâ‚ with total area of 1777.07 ha and class S3waâ‚‚ with total area of 1.318.03 hectares. a maize crops is 1.961,14 ha which consists of land suitability classes S3waâ‚ is 755,52 ha and class S3waâ‚rcâ‚ with total area of 1205.62 ha. The limiting factor is the heaviest average rainfall of 2357.2 mm/year (waâ‚), and soil texture is sandy loam/agak kasar (rcâ‚). a cassava crops is 1961,14 ha which consists of land suitability classes S2waâ‚,â‚‚ with total area of 755.52 ha and class S3tc with total area of 1205.62 ha. The limiting factor is the heaviest average rainfall of 2357.2 mm / year (waâ‚), the number of consecutive dry months 1,41 months / years (waâ‚‚), the average air temperature of 21.8 Â° C (tc). a sweet potato crops is 1961,14 ha with land suitability classes S3waâ‚. The limiting factor heaviest air humidity average of 90.62% (waâ‚). All land groups in research location included in land suitability classes are not suitable (N) for the soybean crops development.